Reconstruction of PAI Learning Strategies Based on a Humanistic Approach in Forming the Spiritual Attitudes of Santri at the Tahfidz Islamic Boarding School - Jihaduddin Akbar Auladi; Yahdinil Firda Nadiroh; Helnanelis; Fitri Hilmiyati (Institut Agama Islam An-Nawawi Purworejo, 2026)
The transformation of education in the digital era demands that Islamic Religious Education (PAI) learning is not only oriented towards mastering religious knowledge, but also capable of forming students' spiritual attitudes holistically. However, PAI learning strategies in various Islamic educational institutions still tend to be teacher-centered and emphasize cognitive aspects, so that the process of internalizing spiritual values ​​has not been optimal. This study aims to reconstruct a PAI learning strategy based on a humanistic approach in shaping the spiritual attitudes of students at the Tahfidz Bani Amir Islamic Boarding School. The study used a qualitative approach with a case study design. Data were obtained through participatory observation, semi-structured interviews, and documentation studies of boarding school caretakers, ustadz, ustadzah, and students selected using a purposive sampling technique. Data analysis was carried out interactively through the stages of data condensation, data presentation, and conclusion drawing. While data validity was tested through source triangulation, technical triangulation, and member checking. The results of the study indicate that the reconstruction of Islamic Religious Education (PAI) learning strategies based on a humanistic approach is built through the integration of five main components, namely learning planning oriented towards spiritual development, student-centered learning, empathetic interpersonal relationships between teachers and students, the habituation of religious culture in Islamic boarding school life, and continuous character evaluation. This strategy has been proven to be able to increase religiosity, discipline in worship, gratitude, responsibility, empathy, and tolerance of students. This study contributes to the development of a conceptual framework for Islamic Religious Education (PAI) learning strategies based on a humanistic approach that strengthens the integration of humanistic theory with the Islamic boarding school education system. These findings imply the importance of reconstructing Islamic Religious Education (PAI) learning that is more participatory and oriented towards the formation of spiritual character. Further research is recommended to test this model on various types of Islamic boarding schools and levels of Islamic education using a mixed approach to obtain a more comprehensive implementation model.